2000
DOI: 10.1111/j.1553-2712.2000.tb00499.x
|View full text |Cite
|
Sign up to set email alerts
|

Resident Perception of Academic Skills Training and Impact on Academic Career Choice

Abstract: Abstract. Objectives: 1) To evaluate residents' perceptions of the quality of training in basic academic skills and the availability and quality of research resources during residency; 2) to evaluate the association between these attitudes and choice of an academic career; and 3) to assess residents' attitudes toward the importance of postgraduate fellowship training for success in an academic career. Methods: A 15-item survey was administered to all U.S. emergency medicine (EM) residents in conjunction with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
1
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 14 publications
4
73
1
5
Order By: Relevance
“…This is an influence that has previously been identified in pediatric and emergency residents. 14,20 Other predictive factors identified in our search of the literature include the number of residents in the program and formal research training in the form of a Masters or PhD. 18,21 Comparison of our results to those obtained from a similar survey in 2009 reveal that research habits, motivations, and attitudes are remarkably stable over time.…”
Section: Cuaj -Original Researchmentioning
confidence: 59%
See 1 more Smart Citation
“…This is an influence that has previously been identified in pediatric and emergency residents. 14,20 Other predictive factors identified in our search of the literature include the number of residents in the program and formal research training in the form of a Masters or PhD. 18,21 Comparison of our results to those obtained from a similar survey in 2009 reveal that research habits, motivations, and attitudes are remarkably stable over time.…”
Section: Cuaj -Original Researchmentioning
confidence: 59%
“…8,9,10,11,12,13 Furthermore, it has been demonstrated that interest in research while high initially, wanes as residency progresses. 14 The concern around the decline in the number and focus of clinician-scientists have led to several important initiatives over the last few decades including increasing early exposure to research at the medical school level, initiating medical scientist training programs, fostering research in sub-specialty fellowships and developing clinician-scientist/early career awards.…”
Section: Introductionmentioning
confidence: 99%
“…17 However, participating in EM research as a resident was found to be positively associated with the choice of an academic career. 18 Prior data has suggested that supporting EM research, including providing funding for research and travel to present that research, positively influences EM residents' choice of a career in academic EM.…”
Section: Discussionmentioning
confidence: 99%
“…2 However, although a significant proportion of EM residents express interest in academia during the early years of their training, this enthusiasm frequently wanes. 3 Evidence exists that formal research educational programs for EM residents can be successful 4 and that when scholarly projects are required of residents, meaningful contributions to the medical literature result. 5 The Royal College of Physicians and Surgeons (RCPS) Specialty Training Requirements in Emergency Medicine require research education and completion of a scholarly project during the 5-year residency ''suitable for peerreviewed publication or presentation at a national academic meeting.''…”
Section: Ré Sumémentioning
confidence: 99%